The Effect of Weight Training on Topspin Shot Accuracy in Club PTM Sasaku Players in 2024 - Reza Amanda Aulia (JOETAL: Journal of Education, Teaching and Learning, 2024)
The basic game of table tennis has three types of spin shots, namely Topspin, Sidespin and Backspin. In its application at the PTM Ssaku club, when making a Forehand Topspin shot, the quality/accuracy of the player's forehand Topspin shot is less than optimal, making it easy for the opponent to return the ball and have difficulty getting points during the match. According to some experts, topspin forehand strokes can be improved by doing weight training. This study aims to evaluate the effect of weight training on the accuracy of TopSpin forehand shots in table tennis athletes trained by the Sasaku Table Tennis Association (PTM Sasaku). The research method used was a paired sample t-test to evaluate changes in athlete performance before and after being given weight training. The results of the analysis show that the calculated t value is greater than the t table, which indicates that there is a significant influence of weight training on the accuracy of the TopSpin forehand stroke. Based on these findings, it can be concluded that weight training tailored to the players' conditions and situations is very necessary to improve their performance. The alternative hypothesis proposed in this research was proven correct, namely that weight training has a significant influence on the accuracy of Topspin forehand strokes in table tennis athletes.